2018
DOI: 10.1590/0034-7167-2016-0574
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of incidents notified in a general hospital

Abstract: Objective: To evaluate the incidents spontaneously notifi ed in a general hospital in Minas Gerais. Method: Retrospective, descriptive, quantitative study performed at a general hospital in Montes Claros -Minas Gerais State. The sample comprised 1,316 incidents reported from 2011 to 2014. The data were submitted to descriptive statistical analysis using Statistical Package for the Social Sciences version 18.0. Results: The prevalence of incidents was 33.8 per 1,000 hospitalizations, with an increase during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
22

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 18 publications
0
27
0
22
Order By: Relevance
“…15 In this environment, cases of near miss were found, mainly due to the supply of medicines that the patients did not use, being intercepted in the last barrier. The findings are compared to the surveys performed in other establishments [7][8] , which identified more errors in the obstetric area and found a higher index related to medications and intravenous fluids, 16 with prevalence in hospitalization units. [7][8]16 It is pointed out that, in relation to the previous use of medicines, this research stood out little compared to the one that found 34% of use for pre-existing diseases, 17 and a Belgian study, 18 that registered 1.4% of drug use by pregnant women.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…15 In this environment, cases of near miss were found, mainly due to the supply of medicines that the patients did not use, being intercepted in the last barrier. The findings are compared to the surveys performed in other establishments [7][8] , which identified more errors in the obstetric area and found a higher index related to medications and intravenous fluids, 16 with prevalence in hospitalization units. [7][8]16 It is pointed out that, in relation to the previous use of medicines, this research stood out little compared to the one that found 34% of use for pre-existing diseases, 17 and a Belgian study, 18 that registered 1.4% of drug use by pregnant women.…”
Section: Resultsmentioning
confidence: 84%
“…13 The satisfaction of the patients with the offered care (95%) was highlighted, according to another study carried out at the same institution, but with a different clientele, which identified precariousness in basic care, extending to the maternal area. 14 It is suggested, however, that strategies that include cultural, structural and organizational influences should be improved in order to promote changes in the multiprofessional team, reflecting their routines, complying with the protocols, conducting trainings, 7,10 favoring patient orientations, sharing decisions and establishing ethical relationships. 5,15 The PSNP proposals include the commitment of professionals and daily reflection on attitudes and behaviors, inserting a model of safe, patient-centered care and with the correct identification of those involved in the environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Estudo realizado em Minas Gerais identificou que as unidades de internação apresentaram o maior número (21,1%) de notificação de incidentes (6) . Na região Sul do Brasil, as unidades de internação também foram os locais com maior frequência (64,8%) de notificação de incidentes (7) .…”
Section: Introductionunclassified